Telecommunications sector and socio-economic development: a comparative analysis of Malaysia and Nigeria - Adeyemi, Raji Abdulwasiu; Jedin, Mohd. Haniff; Abdullateef, Raji; Oluwaseyi, Musibau Hammed (Discovery Publication, 2018)
Telecommunication as a source of communication and information is imperative to the economic exigency of any nation.This is due to the impact it has on the socio-economic development and the general wellbeing of the people.Thus, in this contemporary society, for the other economic sectors to develop, telecommunication has a crucial role to play. It is against this background; that this paper investigates the extent which the telecommunications sector had impacted to the socio-economic development of both Malaysia and Nigeria. To achieve this, the paper adopted secondary source of data such as relevant library materials like journals, textbooks, related published articles on the internet or website and also the use of relevant national newspapers and magazines. This paper comparatively appraises the impact of telecommunications sector on the socio-economic development of both countries over the years. The study revealed that telecommunications sector has impacted immensely to the socio-economic development of both Malaysia and Nigeria. However, the study further discovered that telecoms sector is still contending with various challenges in both countries.The paper therefore recommends that in case of Malaysia, the wireless service providers should adopt migration strategy from prepaid to postpaid vis-à-vis subscribers lock-in method in order to secure their revenue and equally retain their customers due to extreme competition. On the other hand, in Nigeria telecoms providers should invest in customers’ services; and that there is need for government to create enabling environment for the efficient and effective telecommunications services.